HUBUNGAN TINGKAT PENGETAHUAN DENGAN KESIAPAN VAKSINASI COVID-19 PADA USIA PRODUKTIF DI DESA SUKABUNGAH - Sanggu Dedu, Baltasar Serilus; Nuryani, Ami; Hidayati Bunga, Dinda Nur Fajri (STIKes Medistra Indonesia, 2022)
Background: At the end of 2019, there was a pandemic that originated from China, precisely in the city of Wuhan. This pandemic is known as COVID-19. COVID-19 is caused by SARS-CoV-2 (Severe Acute Respiratory Syndrome Coronavirus 2). When compared to SARS in 2003 and MERS in 2012, the spread of this pandemic was much faster. One of the efforts to control the pandemic that is still spreading is the COVID-19 vaccine. Vaccination is an effective prevention of disease transmission and it is the government's obligation to ensure the availability of vaccines. Those who were living in Indonesia aged ³ 18 years is a priority group receiving the vaccine. Research Objectives: The aim of this study is to identify the relationship between knowledge level and COVID-19 vaccination readiness at productive age in Sukabungah village 2021. Research Methods: This research method is a quantitative design using aanalytic research design cross sectional. The population of this study is the productive age community in Sukabungah Village, using the cluster random sampling technique. Research Results : Based on the results of statistical analysis using the chi square test , theobtained p value of 0.000 0.05 was. This shows that H0 is rejected. Conclusion : There is a relationship between the level of knowledge and the readiness of COVID-19 vaccination at productive age in Sukabungah Village in 2021.